Strategic Analysis of the Superior Free-Range Chicken Farming Business of Balitnak (Kub) Using Five Forces - Awang Surya; Verry Surya Hendrawan; Wilarso Wilarso (BASKARA : Journal of Business and Entrepreneurship, 2026)
The Kampung Unggul Balitnak (KUB) chicken farming business has great potential in meeting the community's animal protein needs, but faces various business competition challenges. This study aims to analyze the competitive structure of the KUB chicken business using Porter's Five Forces approach and formulate appropriate strategies to improve competitiveness and business sustainability. This study used a qualitative descriptive method with data collection through in-depth interviews and observations at As-Salaam Farm. The analysis was conducted by assessing five main elements in the Five Forces model, namely the threat of new entrants, supplier bargaining power, buyer bargaining power, threat of substitute products, and the intensity of competition between business actors. The results showed that the threat of new entrants was classified as moderate to high (score 3.6), while the bargaining power of suppliers (2.9) and buyers (2.5) was relatively low to moderate. The threat of substitute products was at a moderate to high level (3.1), with broiler chickens as the main competitor, while the intensity of competition between farmers was low (1.8). These findings indicate that the KUB chicken market structure tends to be open with a level of competition that is not yet intensive, but faces pressure from price-based substitute products. Based on these results, recommended strategies include increasing production efficiency, strengthening product differentiation through quality and market education, and fostering collaboration among farmers. This research contributes to the empirical description of the competitive structure of the KUB chicken business on a smallholder farm scale and offers a practical strategic approach to improving business competitiveness.